Utilization of intelligent systems for managing technological processes and loads - Rakhmonov, Ikromjon; Niyozov, Numon; Qurbonov , Nurbek; Wang, Jian; Isakulov , Sardor (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: automating and digitizing energy consumption in industrial enterprises not only improves energy efficiency but also aids in resource conservation and monitoring of technological processes. Specifically, using intelligent systems in technology and load management enables real-time monitoring of energy consumption, analyzing consumption patterns, and automatically managing consumption at various stages. This significantly enhances the efficiency, reliability, and optimization of production processes. Additionally, digitalization and automation facilitate the correct utilization and distribution of energy resources, supporting sustainable development. Aim: The goal of this study is to develop intelligent and automated systems for managing technological processes and loads, as well as to discuss the benefits of their application. Additionally, using the example of a copper enrichment plant, the study examines load management and the integration of smart technologies to monitor and control energy consumption in real-time. Methods: data collection and analysis, energy monitoring methods, statistical and mathematical analysis, modeling and simulation, experimental research, analytical review, and development of recommendations. Results: at the copper enrichment plant of the Almalyk Mining and Metallurgical Complex (AMMC), the overall structure of energy consumption was analyzed, identifying the technological departments with the highest electricity consumption in the production process. Analysis results showed that the flotation department for copper and molybdenum had the highest energy consumption, accounting for 87.48% of total consumption. To improve energy efficiency, suggestions were made to optimize existing digital monitoring and control systems, as well as recommendations for managing technological processes and loads.